Comparison Of Fracture Torque And Level Of Fracture Of Two Orthodontic Mini-Screw ( AN IN VITRO STUDY) - Omar Sabah Mohammed Jamil; Bahoz Himdad Majeed (Eurasian Journal of Science and Engineering, 2023)
Certain malocclusions may benefit from the use of mini-screw anchoring control during orthodontic treatment. In contrast, the failure of little screws will have a substantial influence on treatment efficiency and effectiveness. Twenty orthodontic mini-implants of (Tomas. Dentaurm. Germany; GNI, Korean) were inspected in an in-vitro study. A digital torque gauge was positioned perpendicular to the bone surface and placed into the 10 mm thick bovine femoral cortical bone in the same manner as mini-implants. The insertion done through the hand driver simulations of insertion intraorally. The Tomas offered a high fracture torque value compared with GNI. GNI gave a high percentage of fracture at an apical level while Tomas gave at the middle of it.